Single-cell analyses identify monocyte gene expression profiles that influence HIV-1 reservoir size in acutely treated cohorts - Philip K. Ehrenberg; Aviva Geretz; Meta Volcic; Taisuke Izumi; Lauren K. Yum; Adam Waickman; Shida Shangguan; Dominic Paquin-Proulx; Matthew Creegan; Meera Bose; Kawthar Machmach; Aidan McGraw; et al. (Nature Communications)
Abstract Eliminating latent HIV-1 is a major goal of AIDS research but host factors determining the size of these reservoirs are poorly understood. Here, we investigate the role of host gene expression on HIV-1 reservoir size during suppressive antiretroviral therapy (ART). Peripheral blood cells of fourteen males initiating ART during acute infection and demonstrating effective viral suppression but varying magnitudes of total HIV-1 DNA were characterized by single-cell RNA sequencing. Differential expression analysis demonstrates increased CD14+ monocyte activity in participants having undetectable HIV-1 reservoirs, with IL1B expression inversely associating with reservoir size. This is validated in another cohort of 38 males comprised of different ancestry and HIV-1 subtypes, and with intact proviral DNA assay (IPDA®) measurements. Modeling interactions show monocyte IL1B expression associates inversely with reservoir size at higher frequencies of central memory CD4+ T cells, linking monocyte IL1B expression to cell types known to be reservoirs for persistent HIV-1. Functional analyses reveal that IL1B activates NF-κB, thereby promoting productive HIV-1 infection while simultaneously suppressing viral spread, suggesting a natural latency reversing activity to deplete the reservoir in ART-treated individuals. Altogether, scRNA-seq analyses reveal that monocyte IL1B expression could decrease HIV-1 proviral reservoirs in individuals initiating ART during acute infection.